THE EFFECT OF QUERCETIN ON MORPHOLOGICAL AND BIOCHEMICAL CHANGES IN RAT LIVER UNDER 270TH DAY CENTRAL DEPRIVATION OF LUTEINIZING HORMONE SYNTHESIS - M.V. Rud; V.I. Shepitko; Ye.V. Stetsuk; O.Ye. Akimov (Проблеми екології та медицини)
The development of the inflammatory process in the liver, including under the influence of hepatitis B and C viruses, is controlled by cells of the immune system, namely, sinusoidal endothelial cells, Ito cells and Kupffer cells. Macrophages play one of the key roles in creating the line of defense. The way in which specific populations of macrophages contribute to liver disease and regeneration is a matter of constant debate. Therefore, identifying the characteristics of these populations of human macrophages is of undeniable value in studying their role in the development of liver pathology. The flavonoid quercetin has capillary-stabilizing properties due to its antioxidant and membrane-stabilizing action. The aim of our study was to determine the changes in immunocompetent liver cells, both qualitative and quantitative, caused by inhibition of central testosterone synthesis in male rats due to the introduction of triptorelin acetate on the 270th day, and the potential effect of quercetin on morphology and liver antigen-presenting cells count against the background of previous administration of triptorelin acetate solution. The experiments were performed on 30 adult male white rats. Rats were divided into 3 groups: control (10), experimental I (10), and experimental II (10). Animals from experimental group I were injected triptorelin acetate subcutaneously at a dose of 0.3 mg of active substance per kg of body weight. In experimental group II, animals received triptorelin acetate in the same dosage and quercetin 100 mg per kg body weight 3 times a week, whereas the control group was administered saline. We conducted biochemical studies in 10% liver tissue homogenate. The main production of superoxide anionic radical (SAR) and superoxide dismutase activity were determined. Peroxynitrite and superoxide anion radical are powerful oxidants that can damage biological polymers (DNA, proteins and biological membranes) and lead to the development of oxidative-nitrosative stress.